The Overaction of the Inferior Oblique Muscle and Associated Vertical Strabismus: Prevalence, Etiology and Diagnosis - Masoud Khorrami-Nejad; Huda Karim; Wisam Hatem; Mustafa Abdullah; Ali Gheibi; Mohammad Ghasemi Boromand (Journal of Modern Rehabilitation)
Introduction: Vertical strabismus, commonly caused by the overaction of the inferior oblique (IO) muscle, is a frequent oculomotor disorder. It affects one-third of all patients with strabismus, with 70% of these cases coexisting with esotropia. Currently, there is no universally accepted method for quantifying the magnitude of IO overaction (IOOA), as existing classifications are subjective and may not be entirely appropriate. Standardization of IOOA classification is crucial to better understand its severity, develop effective treatment strategies, and predict surgical outcomes. The mechanism of action of the IO muscle is complex and varies with the globe's position during contraction. Beyond horizontal and vertical movements, the IO muscle also contributes to torsional eye movements, impacting the diagnosis and treatment of vertical strabismus and cyclotropia. Materials and Methods: The biomechanical properties of the IO muscle and its triple-action characteristics (horizontal, vertical and torsional movements) were analyzed. A review of current diagnostic practices was conducted, emphasizing the need for comprehensive clinical examinations to identify the signs and symptoms of IOOA and determine its severity. Results: Disorders of the IO muscle often result in vertical strabismus and cyclotropia, complicating strabismus treatment. The variability of the IO muscle's mechanism of action highlights the inadequacy of subjective classification systems. Incorporating the triple-action characteristics of the IO muscle into diagnostic evaluations enables a more accurate understanding of IOOA and its clinical manifestations. Conclusion: Standardizing the classification of IOOA is essential for accurately assessing its severity, guiding treatment strategies, and predicting surgical outcomes. Comprehensive diagnostic examinations that consider the triple-action nature of the IO muscle are necessary to improve the management and treatment of patients with IOOA.